2022
DOI: 10.1136/rapm-2022-103534
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided superficial cervical plexus block reduces opioid consumption in patients undergoing craniotomy via suboccipital retrosigmoid approach: a randomized controlled trial

Abstract: IntroductionThe effectiveness of superficial cervical plexus block (SCPB) at decreasing opioid use and improving hemodynamic stability during suboccipital retrosigmoid craniotomy has not been established. The aim of this study is to evaluate the analgesic effect of preoperative ultrasound-guided SCPB for craniotomy via a suboccipital retrosigmoid approach.MethodsThis was a prospective, single-center, randomized, double-blind, parallel-group controlled trial. One hundred and six adult patients undergoing subocc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Out of these 10 studies, improvement in the quality of recovery, as measured by the Quality of Recovery (QoR) questionnaire, was observed in three studies. 101 , 105 , 107 Perioperative opioid consumption was reduced in four studies, 96 , 100 , 103 , 108 pain levels reduced in two studies, 102 , 104 and a shorter time to discharge was observed in one study, 106 all in favour of patients who received a cervical plexus block compared with those who received systemic analgesia only.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Out of these 10 studies, improvement in the quality of recovery, as measured by the Quality of Recovery (QoR) questionnaire, was observed in three studies. 101 , 105 , 107 Perioperative opioid consumption was reduced in four studies, 96 , 100 , 103 , 108 pain levels reduced in two studies, 102 , 104 and a shorter time to discharge was observed in one study, 106 all in favour of patients who received a cervical plexus block compared with those who received systemic analgesia only.…”
Section: Resultsmentioning
confidence: 95%
“…Until 2013, cervical plexus block was mainly studied in relation to thyroid surgery (nine studies). Although thyroid surgery still remains the most extensively studied indication for cervical plexus block with nine RCTs ( n =612), 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 other types of surgery, including middle ear surgery, 102 , 103 parathyroidectomy, 104 , 105 carotid endarterectomy, 106 cervical discectomy and fusion, 107 and craniotomy 108 have also been described.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a single-center, double-blinded RCT of 30 patients undergoing infratentorial or occipital craniotomy, Girard et al 76 reported that postsurgical landmark-based SCPB provided comparable postoperative analgesia to an intravenous opioid technique. A recent RCT of 106 patients undergoing suboccipital retrosigmoid craniotomy by Zeng et al 77 similarly reported reduced 24-hour opioid consumption and reduced incidence of severe postoperative pain among patients who received presurgical, ultrasound-guided SCPB as compared with those who received a sham block.…”
Section: Application Of Regional Anesthesia Techniques In Neuroanesth...mentioning
confidence: 99%